Gas-liquid reaction coprecipitation preparation method of Prussian white positive electrode material

The Prussian white positive electrode material was prepared by gas-liquid reaction co-precipitation method, which solved the problems of fast nucleation rate and poor circulation performance in liquid-liquid co-precipitation reaction, achieved high crystallinity and stability, and improved the circulation life and specific capacity of the material.

CN119569081APending Publication Date: 2025-03-07WUHAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311151742.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing method of preparing Prussian blue compounds in liquid-liquid co-precipitation reactions has problems such as fast nucleation rate, small particle size, and poor circulation performance, resulting in unstable crystal structure.

Method used

The Prussian white positive electrode material was prepared by passing hydrogen cyanide gas into a solution containing soluble divalent transition metal salt and organic acid sodium salt by co-precipitation reaction.

Benefits of technology

The crystallization rate is slowed down, the particle size and crystallinity are improved, the stability and cyclic performance of the crystal structure are enhanced, and the specific capacity and life of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569081A_ABST
    Figure CN119569081A_ABST
Patent Text Reader

Abstract

The invention discloses a gas-liquid reaction coprecipitation preparation method of a Prussian white positive electrode material, and belongs to the technical field of sodium ion batteries. The preparation method comprises the following steps: dissolving soluble bivalent transition metal salt and organic acid sodium salt in deionized water to prepare a solution A; introducing hydrogen cyanide gas into the solution A, and carrying out a co-precipitation reaction at a certain temperature for a certain time to prepare a solid precipitate; and finally, centrifuging, washing and drying the prepared solid precipitate to obtain the Prussian white positive electrode material. The preparation process is simple, and the production cost is reduced; the crystallization rate of the Prussian white positive electrode material is slowed down, and the prepared positive electrode material has high crystallinity, large-particle morphology and excellent structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and particularly relates to a gas-liquid reaction co-precipitation preparation method of a Prussian white positive electrode material. Background Art

[0002] The sustainability of fossil fuels and the intermittency of renewable energy have attracted increasing attention, and low-cost and long-life energy storage systems have become increasingly attractive to power grid systems. Sodium resources are abundant, and compared with lithium-ion batteries, sodium-ion batteries have the potential to be high-performance energy storage devices and can be used as an alternative to lithium-ion batteries. Sodium-ion batteries have attracted particular attention in the fields of science and industry.

[0003] Low-cost Prussian blue compounds (PBAs) with open framework structures have been widely studied as cathode materials for sodium-ion batteries. They are competitive candidates for high energy density applications due to their high average voltage and specific capacity. At the same time, the stability of the PBA framework is ideal for long-life and fast-charging devices.

[0004] The prior art uses a solution-solution coprecipitation (liquid-liquid coprecipitation) reaction to prepare Prussian blue compounds (PBAs), the cyanide source used is sodium ferrocyanide decahydrate, the metal source is a transition metal salt, and the Prussian blue compounds are prepared by liquid-liquid phase coprecipitation. For example, patent application "CN114853033A" provides a method for preparing a Prussian white positive electrode material, first dissolving a divalent manganese salt in deionized water, stirring to a clear liquid, forming a solution A; then dissolving sodium ferrocyanide or potassium ferrocyanide in deionized water, stirring to clarify, forming a solution B; then adding sodium salt to solution B to form a solution C; then mixing solution A and solution C to obtain a suspension D; finally, sealing the suspension D, standing at a constant temperature for aging, filtering out the precipitate obtained by aging, washing and drying, and obtaining a Prussian white positive electrode material.

[0005] However, the liquid-liquid coprecipitation reaction has the following disadvantages: the nucleation rate is fast, the particle size of the material is small, and it is easy to have side reactions with the electrolyte to cause the crystal structure to collapse, resulting in poor cycling performance; due to the fast nucleation rate, there are inevitably a large number of vacancies in the crystal structure, and the crystallinity is poor; in addition, the vacancies will destroy the bridge connection of the Fe-CN-M framework, forming a distorted and defective lattice, which is easy to collapse during the Na insertion / extraction process.

[0006] Therefore, one of the focuses is to study new preparation processes to overcome the shortcomings of liquid-liquid co-precipitation reactions, such as slowing down the crystallization rate, improving particle size, improving crystallinity and crystal structure stability, and improving the specific capacity and cycle performance of positive electrode materials. Summary of the invention

[0007] In order to solve the above technical problems, in a first aspect, the present invention provides a method for preparing a Prussian white cathode material by gas-liquid reaction co-precipitation, comprising the following steps:

[0008] S1. Preparation of solution A: dissolving a soluble divalent transition metal salt and an organic acid sodium salt in deionized water to prepare solution A;

[0009] S2, co-precipitation reaction: hydrogen cyanide gas is introduced into the solution A prepared in step S1, and a co-precipitation reaction is carried out at a certain temperature and time to prepare a solid precipitate;

[0010] S3. Centrifuge, wash and dry the solid precipitate prepared in S3 to obtain a Prussian white positive electrode material.

[0011] Preferably, in step S1, the concentration of the soluble divalent transition metal salt in solution A is 0.05-2 mol / L; and the molar ratio of the organic acid sodium salt to the soluble divalent transition metal salt is 1:1-20:1.

[0012] Preferably, the soluble divalent transition metal salt in step S1 is at least one of copper nitrate, nickel nitrate, manganese nitrate, cobalt nitrate, zinc nitrate, nickel acetate, manganese acetate, zinc acetate, copper sulfate, nickel sulfate, ferrous sulfate, zinc sulfate, manganese sulfate, ferrous chloride, nickel chloride, copper chloride, cobalt chloride and zinc chloride.

[0013] In some embodiments, preferably, the soluble divalent transition metal salt is ferrous sulfate.

[0014] Preferably, the organic acid sodium salt in step S1 is at least one of sodium edetate, sodium citrate, sodium ascorbate, sodium tartrate and sodium lactate.

[0015] In some embodiments, preferably, the organic acid sodium salt is sodium citrate.

[0016] Preferably, the introduction rate of hydrogen cyanide gas in step S2 is 10-100 mL / min; the introduction time of hydrogen cyanide gas is 2 h.

[0017] Preferably, the reaction temperature of the coprecipitation reaction in step S2 is 25 to 80° C. and the reaction time is 12 to 48 hours.

[0018] Preferably, in step S3, the washing solvent is deionized water and anhydrous ethanol; the drying condition is vacuum drying, the drying temperature is 60 to 150° C., and the drying time is 12 to 48 hours.

[0019] In a second aspect, the present invention provides a Prussian white positive electrode material, which is prepared by any gas-liquid reaction co-precipitation preparation method of the Prussian white positive electrode material of the first aspect.

[0020] In a third aspect, the present invention provides a positive electrode sheet, wherein the positive electrode material of the positive electrode sheet is the Prussian white positive electrode material prepared by the preparation method of the first aspect or the Prussian white positive electrode material described in the second aspect.

[0021] In a fourth aspect, a sodium ion battery, the positive electrode material of the sodium ion battery is the Prussian white positive electrode material prepared by the preparation method of the first aspect or the Prussian white positive electrode material described in the second aspect.

[0022] The present invention uses hydrogen cyanide gas as a raw material and adopts a gas-liquid reaction co-precipitation preparation method to prepare a Prussian white positive electrode material. During the preparation process, the nucleation rate of the co-precipitation reaction is slowed down, the crystal particles grow larger, and the occurrence of side reactions is suppressed. The prepared Prussian white positive electrode material has high crystallinity and a large particle morphology, and has reduced vacancies, a more perfect lattice, a more stable crystal structure, and improved The cycle life of the material is improved.

[0023] The invention directly introduces hydrogen cyanide gas into a solution A containing a soluble divalent transition metal salt and an organic acid sodium salt to carry out a coprecipitation reaction, thereby simplifying the preparation process and reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present disclosure will be further described in detail below in conjunction with the accompanying drawings and preferred embodiments, but those skilled in the art will appreciate that these drawings are drawn only for the purpose of explaining the preferred embodiments and therefore should not be used as a limitation on the scope of the present disclosure. In addition, unless otherwise specified, the drawings are only schematically representing the composition or structure of the described objects and may contain exaggerated displays, and the drawings are not necessarily drawn to scale.

[0025] Figure 1 Schematic diagram of the preparation method of Prussian white positive electrode material;

[0026] Figure 2 Scanning electron microscope image of the Prussian white positive electrode material prepared in Example 1;

[0027] Figure 3 Scanning electron microscope image of the Prussian white positive electrode material prepared in Comparative Example 1;

[0028] Figure 4 X-ray diffraction patterns of the Prussian white positive electrode materials prepared in Example 1 and Comparative Example 1;

[0029] Figure 5 Voltage-to-capacity curves of the Prussian white positive electrode materials prepared in Example 1 and Comparative Example 1;

[0030] Figure 6 Cycling performance diagram of Prussian white positive electrode materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0031] The following is combined with Figures 1 to 6 , a detailed description of the present disclosure is given.

[0032] In order to make the purpose, technical solution and advantages of the present disclosure more clear, the present disclosure is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are not used to limit the present disclosure.

[0033] The present invention provides a gas-liquid reaction co-precipitation preparation method of a Prussian white positive electrode material, wherein hydrogen cyanide gas is directly introduced into a solution A containing a soluble divalent transition metal salt and an organic acid sodium salt to carry out a co-precipitation reaction, the preparation process is simple, and the production cost is reduced; the crystallization rate of the Prussian white positive electrode material is slowed down, and the prepared positive electrode material has high crystallinity and a large particle morphology, and exhibits excellent structural stability.

[0034] A gas-liquid reaction co-precipitation preparation method of Prussian white positive electrode material, such as Figure 1 As shown, the following steps are included:

[0035] S1. Preparation of solution A: dissolving a soluble divalent transition metal salt and an organic acid sodium salt in deionized water to prepare solution A;

[0036] S2, co-precipitation reaction: hydrogen cyanide gas is introduced into the solution A prepared in step S1, and a co-precipitation reaction is carried out at a certain temperature and time to prepare a solid precipitate;

[0037] S3. Centrifuge, wash and dry the solid precipitate prepared in S3 to obtain a Prussian white positive electrode material.

[0038] Preferably, in step S1, the concentration of the soluble divalent transition metal salt in solution A is 0.05-2 mol / L; and the molar ratio of the organic acid sodium salt to the soluble divalent transition metal salt is 1:1-20:1.

[0039] Preferably, the soluble divalent transition metal salt in step S1 is at least one of copper nitrate, nickel nitrate, manganese nitrate, cobalt nitrate, zinc nitrate, nickel acetate, manganese acetate, zinc acetate, copper sulfate, nickel sulfate, ferrous sulfate, zinc sulfate, manganese sulfate, ferrous chloride, nickel chloride, copper chloride, cobalt chloride and zinc chloride.

[0040] Preferably, the soluble divalent transition metal salt is ferrous sulfate.

[0041] Preferably, the organic acid sodium salt in step S1 is at least one of sodium edetate, sodium citrate, sodium ascorbate, sodium tartrate and sodium lactate.

[0042] Preferably, the organic acid sodium salt is sodium citrate.

[0043] Preferably, the introduction rate of hydrogen cyanide gas in step S2 is 10-100 mL / min; the introduction time of hydrogen cyanide gas is 2 h.

[0044] Preferably, the reaction temperature of the coprecipitation reaction in step S2 is 25 to 80° C. and the reaction time is 12 to 48 hours.

[0045] Preferably, in step S3, the washing solvent is deionized water and anhydrous ethanol; the drying condition is vacuum drying, the drying temperature is 60 to 150° C., and the drying time is 12 to 48 hours.

[0046] Using sodium citrate as the organic acid sodium salt, the reaction principle of the gas-liquid reaction co-precipitation preparation method of a Prussian white positive electrode material provided by the present invention is:

[0047] 6HCN+2C6H5Na3O7+2FeSO4=Na2Fe[Fe(CN)6]+2Na2SO4+2C6H8O7

[0048] (C6H5Na3O7 is sodium citrate, C6H8O7 is citric acid)

[0049] Example 1

[0050] Dissolve ferrous sulfate heptahydrate in a certain amount of deionized water to obtain a concentration of 0.2 mol L -1 Solution A, adding sodium citrate to solution A, wherein the molar ratio of sodium citrate to ferrous sulfate heptahydrate is 10:1;

[0051] Slowly introduce hydrogen cyanide into solution A at a gas introduction rate of 30 mL / min for 2 h; obtain a suspension by coprecipitation reaction at 30 °C, and age the suspension at this temperature for 24 h to obtain a solid precipitate;

[0052] The solid precipitate was centrifuged and washed three times with water and anhydrous ethanol; the product was dried at 120° C. in vacuum for 18 h to obtain the Prussian white positive electrode material.

[0053] Example 2

[0054] Dissolve ferrous sulfate heptahydrate in a certain amount of deionized water to obtain a concentration of 0.4 mol L -1 Solution A, adding sodium citrate to solution A, wherein the molar ratio of sodium citrate to ferrous sulfate heptahydrate is 8:1;

[0055] Slowly introduce hydrogen cyanide into solution A at a gas introduction rate of 50 mL / min for 2 h; obtain a suspension by coprecipitation reaction at 30° C., and age the suspension at this temperature for 24 h to obtain a solid precipitate;

[0056] The solid precipitate was centrifuged and washed three times with water and anhydrous ethanol; the product was dried at 100° C. in vacuum for 24 h to obtain a Prussian white positive electrode material.

[0057] Example 3

[0058] Dissolve ferrous sulfate heptahydrate in a certain amount of deionized water to obtain a concentration of 0.6 mol L -1 Solution A, adding sodium citrate to solution A, wherein the molar ratio of sodium citrate to ferrous sulfate heptahydrate is 6:1;

[0059] Slowly introduce hydrogen cyanide into solution A at a gas introduction rate of 20 mL / min for 2 h; obtain a suspension by coprecipitation reaction at 30° C., and age the suspension at this temperature for 18 h to obtain a solid precipitate;

[0060] The solid precipitate was centrifuged and washed three times with water and anhydrous ethanol; the product was dried at 100° C. in vacuum for 12 h to obtain a Prussian white positive electrode material.

[0061] Comparative Example 1

[0062] Sodium ferrocyanide decahydrate was dissolved in a certain amount of deionized water to obtain a concentration of 0.2 mol L -1 Solution A;

[0063] Dissolve ferrous sulfate heptahydrate in a certain amount of deionized water to obtain a concentration of 0.1 mol L -1 Solution B, adding sodium citrate to solution B, wherein the molar ratio of sodium citrate to ferrous sulfate heptahydrate is 7:1;

[0064] Solution A was slowly added dropwise to solution B at a dropping rate of 0.8 mL / min, and a suspension was obtained by coprecipitation reaction at 30°C. The suspension was aged at this temperature for 24 h to obtain a solid precipitate;

[0065] The solid precipitate was centrifuged and washed three times with water and anhydrous ethanol; the product was dried at 120° C. in vacuum for 18 h to obtain the Prussian white positive electrode material.

[0066] Comparative Example 2

[0067] Sodium ferrocyanide decahydrate was dissolved in a certain amount of deionized water to obtain a concentration of 0.4 mol L -1 Solution A;

[0068] Dissolve ferrous sulfate heptahydrate in a certain amount of deionized water to obtain a concentration of 0.3 mol L -1 Solution B, adding sodium citrate to solution B, wherein the molar ratio of sodium citrate to ferrous sulfate heptahydrate is 6:1;

[0069] Solution A was slowly added dropwise to solution B at a dropping rate of 1.0 mL / min, and a suspension was obtained by coprecipitation reaction at 30°C. The suspension was aged at this temperature for 36 h to obtain a solid precipitate;

[0070] The solid precipitate was centrifuged and washed three times with water and anhydrous ethanol; the product was dried at 100° C. in vacuum for 12 h to obtain a Prussian white positive electrode material.

[0071] Comparative Example 3

[0072] Sodium ferrocyanide decahydrate was dissolved in a certain amount of deionized water to obtain a concentration of 0.2 mol L -1 Solution A;

[0073] Dissolve ferrous sulfate heptahydrate in a certain amount of deionized water to obtain a concentration of 0.3 mol L -1 Solution B, adding sodium citrate to solution B, wherein the molar ratio of sodium citrate to ferrous sulfate heptahydrate is 7:1;

[0074] Solution A was slowly added dropwise to solution B at a dropping rate of 0.8 mL / min, and a suspension was obtained by coprecipitation reaction at 30°C. The suspension was aged at this temperature for 24 h to obtain a solid precipitate;

[0075] The solid precipitate was centrifuged and washed three times with water and anhydrous ethanol; the product was dried at 120° C. in vacuum for 12 h to obtain the Prussian white positive electrode material.

[0076] Experimental Results and Discussion

[0077] The present invention performs scanning electron microscopy on the Prussian white positive electrode material prepared in Example 1. Figure 2 As shown, the morphology of the Prussian white positive electrode material prepared in Example 1 is secondary cubic particles, the primary particles are 1 μm, and the secondary particles are 25 μm.

[0078] The present invention performs scanning electron microscopy on the Prussian white positive electrode material prepared in Comparative Example 1. Figure 3 As shown, the morphology of the Prussian white positive electrode material prepared in Comparative Example 1 is secondary cubic particles, with primary particles of 1 μm and secondary particles of 6 μm.

[0079] The particles of Comparative Example 1 are much smaller than those of Example 1.

[0080] The present invention performs X-ray diffraction characterization on the Prussian white positive electrode materials prepared in each embodiment of Example 1 and Comparative Example 1, as shown in FIG. Figure 4As shown, the Prussian white positive electrode material prepared in Example 1 and the Prussian white positive electrode material prepared in Comparative Example 1 both present a monoclinic phase structure; the diffraction peak intensity of the Prussian white positive electrode material prepared in Example 1 is higher than the diffraction peak of the positive electrode material prepared in Comparative Example 1, therefore, the crystallinity of the positive electrode material prepared in Example 1 is better than the crystallinity of the positive electrode material prepared in Comparative Example 1.

[0081] The present invention also conducted voltage specific capacity tests on the Prussian white positive electrode materials prepared in each embodiment of Example 1 and Comparative Example 1. Figure 5 As shown, the specific capacity of the Prussian white positive electrode material prepared in Example 1 at a current of 0.3C is 131.5 mAh / g, and the specific capacity of the Prussian white positive electrode material prepared in Comparative Example 1 at a current of 0.3C is 123.8 mAh / g; the specific capacity of the Prussian white positive electrode material prepared in Example 1 is better than the specific capacity of the Prussian white positive electrode material prepared in Comparative Example 1.

[0082] The present invention performs cycle performance test on the Prussian white positive electrode materials prepared in each embodiment of Example 1 and Comparative Example 1. Figure 6 As shown, the Prussian white positive electrode material prepared in Example 1 has a specific capacity of 96.6 mAh / g after 400 cycles at a current of 1C, and a capacity retention rate of 87.2%; the Prussian white positive electrode material prepared in Comparative Example 1 has a specific capacity of 65.9 mAh / g after 150 cycles at a current of 1C, and a capacity retention rate of 57.6%; the cycle stability of the positive electrode material prepared in Example 1 is significantly enhanced.

[0083] The present invention respectively tests the voltage specific capacity and cycle performance of the Prussian white positive electrode materials prepared in Example 2 and Comparative Example 2. The specific capacity of Example 2 at a current size of 0.3C is 127.2mAh / g, and the specific capacity of Comparative Example 2 at a current size of 0.3C is 119.5mAh / g; at a current size of 1C, the specific capacity of Example 2 after 400 cycles is 91.4mAh / g, and the capacity retention rate is 84.6%; at a current size of 1C, the specific capacity of Comparative Example 2 after 150 cycles is 60.8mAh / g, and the capacity retention rate is 53.2%.

[0084] The specific capacity of the Prussian white positive electrode material prepared in Example 2 is better than that of the Prussian white positive electrode material prepared in Comparative Example 2; the cycle performance of the Prussian white positive electrode material prepared in Example 2 is significantly enhanced relative to that of the Prussian white positive electrode material prepared in Comparative Example 2.

[0085] The present invention respectively tests the voltage specific capacity and cycle performance of the Prussian white positive electrode material prepared in Example 3 and Comparative Example 3. The specific capacity of Example 3 at a current size of 0.3C is 130.4 mAh / g, and the specific capacity of Comparative Example 3 at a current size of 0.3C is 116.3 mAh / g; at a current size of 1C, the specific capacity of Example 3 after 400 cycles is 93.7 mAh / g, and the capacity retention rate is 85.3%; at a current size of 1C, the specific capacity of Comparative Example 3 after 150 cycles is 58.8 mAh / g, and the capacity retention rate is 51.8%.

[0086] The specific capacity of the Prussian white positive electrode material prepared in Example 3 is better than that of the Prussian white positive electrode material prepared in Comparative Example 3; the cycle performance of the Prussian white positive electrode material prepared in Example 3 is significantly enhanced relative to that of the Prussian white positive electrode material prepared in Comparative Example 3.

[0087] The Prussian white positive electrode material prepared by the gas-liquid reaction co-precipitation preparation method using hydrogen cyanide gas as a raw material has high crystallinity and a large particle morphology, reduced vacancies, a more perfect lattice, a more stable crystal structure, and significantly enhanced cycle life of the material.

[0088] The present disclosure is described in detail above. The principles and implementation methods of the present disclosure are described in detail using specific examples in the present disclosure. The description of the above embodiments is only used to help understand the present disclosure and its core ideas. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present disclosure, several improvements and modifications can be made to the present disclosure, and these improvements and modifications also fall within the scope of protection of the claims of the present disclosure.

Claims

1. A gas-liquid reaction co-precipitation preparation method of Prussian white cathode material, characterized in that: The steps include: S1. Preparation of solution A: dissolving a soluble divalent transition metal salt and an organic acid sodium salt in deionized water to prepare solution A; S2, co-precipitation reaction: hydrogen cyanide gas is introduced into the solution A prepared in step S1, and a co-precipitation reaction is carried out at a certain temperature and time to prepare a solid precipitate; S3. Centrifuge, wash and dry the solid precipitate prepared in S3 to obtain a Prussian white positive electrode material.

2. The gas-liquid reaction co-precipitation preparation method of Prussian white cathode material according to claim 1, characterized in that: In step S1, the concentration of the soluble divalent transition metal salt in solution A is 0.05-2 mol / L; the molar ratio of the organic acid sodium salt to the soluble divalent transition metal salt is 1:1-20:

1.

3. The gas-liquid reaction co-precipitation preparation method of Prussian white cathode material according to claim 1, characterized in that: In step S1, the soluble divalent transition metal salt is at least one of copper nitrate, nickel nitrate, manganese nitrate, cobalt nitrate, zinc nitrate, nickel acetate, manganese acetate, zinc acetate, copper sulfate, nickel sulfate, ferrous sulfate, zinc sulfate, manganese sulfate, ferrous chloride, nickel chloride, copper chloride, cobalt chloride and zinc chloride.

4. The gas-liquid reaction co-precipitation preparation method of Prussian white cathode material according to claim 1, characterized in that: In step S1, the organic acid sodium salt is at least one of sodium ethylenediaminetetraacetate, sodium citrate, sodium ascorbate, sodium tartrate and sodium lactate.

5. The gas-liquid reaction co-precipitation preparation method of Prussian white cathode material according to claim 1, characterized in that: In step S2, the rate of introduction of hydrogen cyanide gas is 10-100 mL / min; the time of introduction of hydrogen cyanide gas is 2 h.

6. The gas-liquid reaction co-precipitation preparation method of Prussian white cathode material according to claim 1, characterized in that: The reaction temperature of the coprecipitation reaction in step S2 is 25 to 80° C. and the reaction time is 12 to 48 hours.

7. The gas-liquid reaction co-precipitation preparation method of Prussian white cathode material according to claim 1, characterized in that: In step S3, the washing solvents are deionized water and anhydrous ethanol; the drying conditions are vacuum drying, the drying temperature is 60 to 150° C., and the drying time is 12 to 48 hours.

8. A Prussian white positive electrode material prepared by the gas-liquid reaction co-precipitation preparation method of the Prussian white positive electrode material according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: The positive electrode material of the positive electrode sheet is the Prussian white positive electrode material prepared by the preparation method of any one of claims 1 to 7 or the Prussian white positive electrode material described in claim 8.

10. A sodium ion battery, characterized in that: The positive electrode material of the sodium ion battery is the Prussian white positive electrode material prepared by the preparation method of any one of claims 1 to 7 or the Prussian white positive electrode material according to claim 8.

Citation Information

Patent Citations

  • Synthesis process and application of Prussian white

    CN114853033A